Relation between Preinfarction Angina and Coronary Collateral Circulation in Patients with Acute Myocardial Infarction - Achmad Shidiq; Syarief Hidayat; Januarsih Iwan Rachman (Faculty of Medicine Universitas Padjadjaran, 2016)
Background: Coronary collateral circulation conduits an alternative blood flow to the ischemic myocardium in the setting of coronary artery occlusion which can prevent the infarction area to extend more widely. Well-developed coronary collaterals are closely related with the presence of preinfarction angina. However, the duration of preinfarction angina which can induce well-developed coronary collateralization is in controversy. The aim of this study was to evaluate the relation between duration of preinfarction angina and coronary collaterals circulation in patients with acute myocardial infarction.Methods: This cross-sectional study was conducted from May to November 2013 in Dr. Hasan Sadikin General Hospital, Bandung, Indonesia. Seventy three acute myocardial infarction (AMI) patients were included in the study. The patients were divided into Group 1 (<7 days) and Group 2 (≥7 days) based on their preinfarction angina history. The coronary collaterals were assesed and graded as good (Rentrop score 2−3) and poor (Rentrop score 0−1).Statistical analysis was performed using the chi-square test.Result: The presence of a well-developed coronary collateral was not significantly different in <7days than ≥7 days duration of preinfarction angina [50.8% v 75.0%, p=0.124].Conclusions: There is no relation between the duration of preinfarction angina and coronary collaterals circulation in patients with acute myocardial infarction. [AMJ.2016;3(1):28–33]DOI: 10.15850/amj.v3n1.709